Carlos Monsiváis: lector de imágenes (De la construcción de la identidad nacional al mito personal) - Gallardo Luque, Iván (Anales de Literatura Hispanoamericana, 2003)
Carlos Monsiváis has changed the ways to reflect mexican reality by modeling actuality with all its conflicts of development and anacronicity, in a detailed portrait of the Iberoamerican stetc of things. Like the iconoclastic and poligraphic that he is, he approached in his works, the study of mass-medias, especially cinematographic genres, starsystem and television, as privileged mirrors from which to sustain society that generate and consume them.